Fundamentos cinemáticos para el diseño de las máquinas y mecanismos - Angeles Älvarez, Jorge; Roth, Bernard; Herve, Jacques M. (My University, 1981)
Abstract: in this paper, an “equivalent screw triangle” is traduced from wich the design equations can be determined for any combinations of the helical, cylindrical, revolute, spherical, and prismatic joints for both finitely and infinite smally separated position problems in kinematic synthesis. In addition to presenting a new and unified approach to previously solved problems, this paper can be applied to the design of binary links for rigid body guidance, function generation and similar problems. A numerical example illustrating the design of H-H links is included.
Keywords: cinemática; rotación; cálculo; velocidad; ejes